Attachment Need and Fear of Loneliness in Close Relationships - (:unkn) unknown (ICLEL CONFERENCES, 2016)
The main purpose of the present study is to investigate the relationship between attachment need in close/romantic relationships and fear of loneliness. The study is designed according to mixed research approach. Quantitative and qualitative research instruments were used respectively. Firstly Experience in Close relationships Inventory (ECR) and Adult Separation Anxiety Survey (ASA) were applied to 200 adult individuals aged between 25-35. In the second phase, 30 interviews were conducted with voluntary participants. Data gathered through quantitative and qualitative instruments were interpreted and evaluated together. Independent Samples T-test and Pearson Correlation analyses were conducted for examining quantitative data. Significant difference was found in ASA questionnaire and avoidance dimension of ECR Inventory scores between the groups formed according to gender, relationship status and relationship history. And also, significant differences were detected in both dimensions of ECR and ASA scores between participants who experienced fear of losing someone during a relationship and who did not. Pearson correlation analysis shows that there is a significant relationship between ASA questionnaire and anxiety dimension ECR Inventory. There is also positive and significant relationship between anxiety and avoidance dimensions of ECR. In qualitative phase, phenomenological research design was used. The analysis shows that participants have the fear of losing their partners and family members. Besides, they associated their fear of loneliness with leaving home and being abandoned by parents. Meanings attributed to presence of a partner consist of four themes: safety, sharing life, joy and love. Another finding indicates that absence of a partner leads to feeling incomplete, not being worthy of love and loneliness. Some participants described absence of a partner as a positive process. Possible feelings attributed to hypothetical ending of current relationship are expressed in seven themes: incompleteness, fear, unhappiness, relief, hopefulness for future, disappointment and loss of trust. Loneliness and attachment processes in relationships are not only related to each other, but also they may have significant roles in close relationships. It is suggested to consider dynamics of these concepts and help individuals develop through therapeutic interventions in order to strengthen close relationships, which can deeply affect individuals' existence in personal and social mental health.
Keywords: Attachment Need; Close Relationships; Fear of Loneliness; YOUNG ADULTHOOD; SOCIAL SUPPORT; INTIMACY; SATISFACTION; ADOLESCENCE; EXPLORATION; COMMITMENT; IDENTITY; MODEL